Fostering learning strategies in universities to prepare a self-regulated workforce. (17th July 2008) - Zellweger Moser, Franziska; Hasanbegovic, Jasmina; Metzger, Christoph
Due to directive teaching experiences at schools, students are not regarded as active, self-regulated learners. In particular, Time Management (TMT) is reported as a critical but deficiently developed Learning Strategy (LS) not only by students but also by working practitioners. Little attention is paid to fostering those LSs at universities which are important for future work and workplace learning. Thus, the aim of this paper is to identify possibilities to develop LSs within university education. It is reported from an analysis of multiple studies applying a multiscale instrument to diagnose LSs. A case study provides insights into TMT strategies and how students perceive the support provided by the institution. It may be concluded that formal education is not sufficiently addressing the development of suitable skills for work life. Universities should pay attention to the environment in which students are immersed, stimulate reflection and promote collaboration among students.